CORROSION-RESISTANT FOR HYDRAULIC CONCRETE CONSTRUCTION - , Е. В. (Municipal economy of cities. Series: «Economy science», 2013)
The results of studies aimed at obtaining hydraulic concrete increased corrosion resistance by modifying the polymer additives.